Color Image Compression Using Wavelet Compression and Zero-MeanCoding - Azeez, Nassr; Al-Taie, Inas (Iraqi Journal of Science, 2024)
Thousands pictures require a very large amount of storage. So differenttechniques of digital image compression is used to reduce the storage requirementsfor these images. In this paper an adaptive compression method applied on colorimage. Firstly the color image is transformed to the RGB system, and then convertsthe color data to a luminance/chrominance color space (YIQ).The adaptivecompression method is applied on Y. The image may contain a uniform region andedge region; the uniform regions compress depending on zero-mean coding and theedge region compress depending on Daubechies wavelet transform, then returnedthe final image to RGB system. The proposed algorithms has many advantageswhich make it very efficient, these are, low bit rate, low computational complexity,fast processing and edge preservation with good reconstructed image quality.